Tabloidyzacja bluźnierstwa. Strategie medialne w debacie publicznej o granicach wolności artystycznej i obrazie uczuć religijnych - Leszczuk-Fiedziukiewicz, Anna (Studia Prawnoustrojowe, 2019)
“Pop-cultural profanities” that are described in the article cause social and criminological consequences. They inform about cultural norms and point to the problem of freedom of expression in democratic societies as well as the subtlety of meanings of religious symbols used by artists in theatreperformances. This issue has a broader social context. On the one hand, there is growing secularization and phenomenon of “privatization of religion”in Europe. On the other hand, the social movements are grounded their cultural identity on religion. The polarization of these two perspectives i easily noticed in the media content. The more shocking artists are, the more innovative Christians reaction is. Outrage usually takes the form of street protests and demonstrations, occupying theatres and public places. Many ases end with lawsuits and debates about the boundaries of art. The content of this article are the media narratives used by professional and amateur journalists in the public debate on the plays of Golgota Picnic (2014) and Klątwa (2017).